Is there any association between facial type and mandibular dental arch form in subjects with normal occlusion? - Luiz Renato Paranhos; Adilson Luiz Ramos; Eduardo de Novaes Benedicto; Liliana Àvila Maltagliati; Maurício de Almeida Cardoso; Leopoldino Capelozza Filho (Universidade Estadual de Maringá, 2014)
http://dx.doi.org/10.4025/actascihealthsci.v36i1.17668 The aim of this study was investigate the association between the mandibular arch morphology and the facial type of Brazilian Caucasians with natural normal occlusion. For this, we used a sample comprised of lateral radiographs and respective dental casts of 51 individuals (21 male and 30 female), presenting at least 4 of the 6 Andrews' keys to normal occlusion without previous orthodontic treatment. Angle's first molar relationship was considered indispensable for the sample. The facial type was defined by two cephalometric measurements (SN.SGn and SN.GoGn). After scanning the models (3D) and radiographs, the images were evaluated by 12 orthodontists. A modified Kappa test evaluated the agreement between examiners to classify the morphology of the dental arch. The chi-square test was used to verify the association between the facial type (dolichofacial, mesofacial, or brachyfacial) and the dental arch morphology (square, oval, or tapered), using significance level of 5%. Casual and systematic errors (p > 0.05) showed no significant results and the Kappa test showed significant agreement among examiners for the dental arch form (0.55) with a p < 0.001, considered as 'moderate'. The chi-square test indicated no significant association. The null hypothesis was accepted, as the facial type was not associated with dental arch morphology in individuals with normal occlusion.